Juridical Insight: Resolving Interim Village Head Election Disputes in Sumbawa Regency - Dianto, Dianto (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2023)
The election of village heads is a form of popular sovereignty. However, the village head election process cannot be separated from disputes, so a dispute resolution scheme is needed that provides justice. This research is normative research with a conceptual approach, statutory approach and case approach. The case that is the focus of this research is the case of the interim village head election in Labangka Satu Village, Labangka District, Sumbawa Regency, where in the village head election process the village head election supervisory committee was not appointed as the institution that resolves village head election disputes. In the absence of a supervisory committee for Village head elections, parties who object to the results of the Village head election report to the Regent, but regulations at the regional level do not regulate the Regent's authority to resolve disputes over Village head elections. The results of this research are (1) Settlement of interim village election disputes in Sumbawa Regency is the same as the mechanism for resolving village election disputes simultaneously through a supervisory committee but is not regulated in regional regulations or other regulations regarding the Regent's obligation to resolve village election disputes as mandated in article 37 paragraph (6) of the Law. number 6 of 2014 concerning Villages. (2) The legal consequences if the Regent appoints an elected village head without first resolving the dispute is that the regent's decision is null and void because resolving the dispute is an obligation which is an absolute requirement in the village head election process. The conclusion of this research shows that legally there is no regulated scheme for resolving disputes over interim village elections so that the legal consequences if the Regent appoints an elected village head without first resolving the village election dispute is that the Sumbawa Regent's decision is null and void. This research suggests (1) the Regional Government of Sumbawa Regency needs to regulate the obligations of the Regent to resolve village head election disputes, (2) the Regent of Sumbawa can form a special team to resolve village election disputes to carry out its obligations to resolve village election disputes.